Realizing a Child Friendly City as Protection towards Children in Indonesia - Ahmad Musthafa Azhom (Constitutionale, 2021)
The future of human civilization are in the hand of children nowadays. In order to. In order to deliver the better future human civilization the government should create a friendly place for children to live on and growth. By that the government of Indonesia has created the regulations where the focus are to protect the rights of the children. In this research aims to know how far the regulations of child-friendly city in the law regulations have reached. This research uses a normative juridical approach, by examining the regulation of a child-friendly city through the laws and regulations. The data analyzed is secondary data in the form of doctrine or opinion of constitutional law experts, and books, including scientific journals, primary data in the form of UUD 1945 and the law regulations. The data obtained were analyzed deductively and thoroughly by using the low systematic research and the hierarchical level of the low regulations. From the research results, it is found that the Government has made efforts in developing Child Friendly City. Facilitated by the relevant law regulations that are built on the basis of commitment from each network actor to create a Child Friendly City so the policy can run effectively, efficiently and on target. with the character of each related institution in each child protection program, creating the opportunity for the creation of a child-friendly city by accepting ideas and suggestion for the policy of Child Friendly City to build the same perception..